Out of character - Albert, Annabeth (True colors, 2021)
"When Milo Lionetti loses his brother's prized deck of Odyssey cards, he'll do anything to replace them-including begging for help from his ex-best friend, Jasper Quigley. Jasper's got bigger things to worry about than the boy who broke his young heart, and if Milo wants his help, he's going to have to join Jasper in making the children's hospital charity ball the best ever. But as the two boys don cosplay for the kids and hunt for rare cards, nostalgia for their lost friendship may turn into something even warmer..."--